Fenton and Photo-Fenton Processes for the Degradation of Atrazine: A Kinetic Study - Benzaquén, Tamara Belén (2014)
BACKGROUND: This study is focused on the kinetic modelling of the Fenton and photo-Fenton degradation of a model pollutant (atrazine) in aqueous solution. The effects of hydrogen peroxide and ferric ion concentrations as well as those of radiation level on the degradation processes have been investigated. RESULTS: The experimental work was performed in a well-stirred tank laboratory reactor irradiated from both sides with two tubular UV-lamps. The reaction rate expressions were derived from an accepted reaction mechanism, explicitly taking into account the local volumetric rate of photon absorption inside the photoreactor. The proposed kinetic model was able to reproduce the combined effects of changing the ferric iron concentrations, hydrogen peroxide to atrazine molar ratios and radiation level on the pollutant degradation rate. Model predictions were compared with experimental data and a good agreement was obtained. The maximum root mean square error (RMSE) for all the estimations was < 2.5 %. CONCLUSIONS: The results obtained indicate that Fenton and photo-Fenton processes are possible ways to improve the biodegradability of a wastewater containing commercial atrazine.